2007
DOI: 10.1007/s00405-007-0501-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of postoperative measures after sinus surgery

Abstract: To compare the long-term effects of different postoperative treatment regimes after functional endoscopic sinus surgery (FESS), we performed a randomized controlled trial. Inclusion criteria were chronic rhinosinusitis with (CRSwNP) or without (CRS-NP) bilateral nasal polyps and acute recurrent rhinosinusitis (ARR). All patients (male/female = 56/65; mean age = 42.8 years; age range 18-73 years) underwent sinus surgery for the first time. The patients included in 2004 were allocated to a packing in middle meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 17 publications
3
40
0
1
Order By: Relevance
“…The study by Bugten et al24 (level 1b) demonstrated that postoperative sinus cavity debridement resulted in reduced crust and middle meatal adhesion rates at 3 months follow‐up. In 2008, Bugten et al28 reported the long‐term results of their debridement group and demonstrated that the initial short‐term improvements were stable after 56 weeks. The remaining 2 level 1b studies identified in this review attempted to elucidate the ideal timing of postoperative debridement.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Bugten et al24 (level 1b) demonstrated that postoperative sinus cavity debridement resulted in reduced crust and middle meatal adhesion rates at 3 months follow‐up. In 2008, Bugten et al28 reported the long‐term results of their debridement group and demonstrated that the initial short‐term improvements were stable after 56 weeks. The remaining 2 level 1b studies identified in this review attempted to elucidate the ideal timing of postoperative debridement.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative steroids have been shown to improve endoscopic appearance, but risks of corticosteroids have to be considered and this has resulted in more conservative use after sinus surgery, especially in non‐polyp patients . Benefit of endoscopic debridement after endoscopic sinus surgery has been demonstrated in the literature, with the optimal timing of the first debridement at 1 week . Similarly, our study demonstrates that most respondents (72.6%) always or often performed endoscopic debridement, and most (78.1%) had patients follow up in less than 2 weeks for the first postoperative visit.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although many patients receive nasal surgery to improve the sense of smell, relatively little research has been performed to investigate determinants of postoperative outcome. To be specific, many studies either were performed with relatively small samples, 2,3 or collected only the patients' ratings of olfactory function, 4 although these measurements have been demonstrated to be notoriously unreliable. 5 Recent work 6 indicated that postoperative success in terms of olfactory function is best in female patients and in those with a high degree of polyposis and aspirinintolerance.…”
Section: Introductionmentioning
confidence: 99%